Nitrogen oxyanion reduction by Co(ii) augmented by a proton responsive ligand: recruiting multiple metals. Issue 23 (1st June 2020) - Cabelof, Alyssa C.; Carta, Veronica; Chen, Chun-Hsing; Caulton, Kenneth G.
Abstract : Deoxygenation of nitrite oxygen with divalent cobalt was achieved using (PNNH)CoCl2, carrying a pyridyl pincer ligand with one P( t -Bu)2 arm and one pyrazole arm. Abstract : Deoxygenation of nitrite oxygen with divalent cobalt was achieved using (PNNH)CoCl2, carrying a pyridyl pincer ligand with one P( t -Bu)2 arm and one pyrazole arm. Reaction of (PNNH)CoCl2 with NaNO2 at a 2 : 5 mole ratio promptly forms equimolar (PNNH)Co(NO2 )3 and (PNN)Co(NO2 )(NO), {CoNO}8 with the lost ligand proton combined with removed oxo as hydroxide. These two Co III products are characterized, showing a bent CoNO unit as the fate of the reduced nitrogen. DFT calculations are consistent with two one-electron Co II reductants binding to one NO2 − bridge, then proton transfer being needed for facile N/O bond scission. A species detected by low temperature execution of this reaction contains cobalt in two oxidation states with an N, O bridging nitro group and pincer ligands that have been deprotonated, showing the active participation of the proton responsive ligand.